Problem Posing as a Learning Model to Improve Primary School Students' Mathematics Learning Outcomes in Gayo Lues - Rahmah, Sinar; Lubis, Azmil Hasan (Journal of Indonesian Primary School, 2024)
Mathematics is one of the most important subjects for students to master in elementary school. However, there are many students who do not like mathematics learning which has an impact on their low learning outcomes in mathematics learning. The results of the preliminary study of this study indicate that students' mathematics learning outcomes are still very low. This is evidenced by the results of the documentation of student grade lists, there are still many students who do not reach the minimum completion criteria set by the school. This study aims to improve students' mathematics learning outcomes in elementary schools by applying the problem posing model. This study is a classroom action research with the Kemmis & Mc Taggart design. This study was conducted in three cycles with the stages of each cycle being planning, action, observation and reflection. The subjects of this study were fourth grade elementary school students. Data were collected using test and observation techniques. The data obtained were then analyzed using descriptive statistical techniques. The results of the study indicate that the problem posing model can improve students' mathematics learning outcomes in elementary schools. This is evidenced by looking at the results of the first cycle test which achieved a classical completion percentage of 52.63%. Then in the second cycle the classical completion percentage increased to 68.42%. The achievement in the third cycle increased again to 84.21%. The results have reached the target indicator of the success of this study. Thus, the problem posing model can be used as an alternative for use by teachers in mathematics learning in elementary schools.